A Review Potential Radioprotective Mechanism of Molecular Hydrogen via Regulation of Cellular Signaling Pathways - JAMAN, MD SADIKUJ (RADINKA JOURNAL OF HEALTH SCIENCE, 2025)
Molecular hydrogen is a biologically significant molecule with diverse applications in the treatment and prevention of diseases in both humans and animals. Exposure to radiation from medical procedures such as CT scans, X-rays, and radiotherapy can disrupt normal cellular functions and cause abnormal cellular behavior. These radiation-induced effects are linked to multiple signaling pathways that contribute to cellular damage. Molecular hydrogen has emerged as a promising therapeutic agent capable of mitigating radiation-related injuries and supporting the recovery of affected cellular pathways. A thorough literature search was carried out using databases including Google Scholar, PubMed, Scopus, and ScienceDirect to obtain detailed information on radiation-related cellular signaling pathways and the possible radioprotective roles of molecular hydrogen. We identified several cellular signaling pathways associated with radiation exposure. Among them are the cell cycle checkpoint pathway, DNA repair pathways, EGFR/tyrosine kinase-mediated pro-survival signaling, Rac1-mediated signaling, ERK1/2 signaling, PI3k/AKT signaling, NF-kB signaling, autophagy signaling, HIF-1α signaling, and YAP signaling pathways. Molecular hydrogen can be administered through various delivery methods and supports the recovery of many of these pathways. It also exhibits multiple beneficial effects in both humans and animals, including antioxidant, anti-apoptotic, anti-inflammatory, and gene regulatory properties. Molecular hydrogen has emerged as one of the most promising radioprotective agents, given that radiation exposure is a major contributor to carcinogenesis and cellular damage. The objective of this review is to elucidate the cellular signaling pathways influenced by radiation and to examine the potential radioprotective mechanisms of molecular hydrogen in mitigating radiation-induced biological effects.